Rhetorical Pattern in Research Article Introduction Section Written by Indonesian Authors - Angela Valentiara Giofanny; Lulus Irawati; Erlik Widiyani Styati (International Journal of Education, Vocational and Social Science, 2025)
The purpose of this study is to describe the rhetorical patterns seen in research articles produced by Indonesian authors' introductions. This study used document analysis as a part of qualitative approach. Twenty research articles (RAs) in the introduction section that were uploaded to SINTA served as the study's data sources. Research publications in the fields of literature, linguistics, and pedagogy written by Indonesians served as the data sources. The analysis used Swales's (2004) CARS theory to understand the rhetorical structure of article introductions. The findings reveal differences in the introductions' writing styles across the examined articles. Step 3: Occupying the Niche and Step 1: Outlining the Purpose or Stating the Nature of the Research were the two most important steps in the CARS structure. 48 data points, or 50% of the total data analyzed, are included in Step 3, indicating the significance of the authors' assertions regarding the presence and applicability of their research. In the meantime, Step 1 produced 15 data points (19.2%), suggesting that authors try to clearly state the goal and subject matter of their research. Furthermore, it was found that some phases, such Step 6 Move 3: Stating the Value of the Present Research and Step 7 Move 3: showing the Structure of the Present Research Paper, were completed less frequently, showing differences in rhetorical approach. This study suggests that Indonesian authors try to be open and honest about the goal of their research while also emphasizing the importance and contribution of their work. To summarize, Indonesian writers' use of rhetoric in research paper introductions reflects an effort to promote openness and clarity in articulating the study's purpose, which is crucial for improving scientific communication and comprehension.